The nominative technique: a simple tool for assessing illegal wildlife consumption. Issue 2 (2nd March 2022) - Davis, Elizabeth Oneita; Crudge, Brian; Glikman, Jenny Anne
Abstract: The aim of our study was to test the efficacy of the nominative technique for estimating the prevalence of wildlife part use within a small sample. We used the domestic consumption of bear Ursus thibetanus and Helarctos malayanus parts in Lao People's Democratic Republic (Laos) as a case study and performed 179 semi-structured interviews in Luang Prabang, northern Laos, in August 2017 and April 2019. We also assessed whether the specialized questioning of the nominative technique could be used for qualitative data collection methods, such as semi-structured interviews. The technique theoretically ensures more accurate statements of illegal wildlife consumption by maintaining the anonymity of an individual's sensitive behaviour through asking about the behaviour of peers. We also directly asked about participants' use of bear parts. The nominative technique suggested that c. 11% of the participants' peers used bear parts, whereas respondents' direct admittance of using bear parts was approximately double, at 23%. Use of bear parts appears not to be sensitive in northern Laos. In addition, we found a strong association between responses to questioning using the nominative technique and direct questioning, indicating that users of bear parts have social networks with higher levels of use. This lends supports to theories that use of wildlife products is directly influenced by social group. The underreporting resulting from use of the nominative technique indicates the high variability of response that can occur within small samples. However, our results show that the nominative technique may be a simple, useful tool for triangulating data, assessing users' integration into social networks of use, and assessing changes in behaviour prevalence.